2006
DOI: 10.1007/s10646-006-0057-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of culture conditions and mother’s age on the sensitivity of Daphnia magna Straus 1820 (Cladocera) neonates to hexavalent chromium

Abstract: Daphnia magna is a freshwater cladoceran used worldwide as test organism in aquatic toxicity assays. In Mexico there is a test protocol for this species; nevertheless, some aspects of the controlled neonate production, as well as the possible consequences of the reproducers' culture conditions on the response of neonates to the toxic substance, are not completely known. In the present study, we evaluated the effect of temperature and photoperiod on the acute toxicity of CrVI in D. magna neonates, aimed at prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 30 publications
(21 reference statements)
0
12
1
2
Order By: Relevance
“…Table 2 summarizes some results of 48 h-LC 50 values for metals to daphnid species, however, the different physical and chemical parameters of culture media (hardness, and pH), make comparisons difficult. We obtained 48 h-LC 50 values for cadmium and chromium to D. similis lower than those that have been obtained for other daphnid species by Fargasová (1994), Barata et al (1998), Taylor et al (1998), Dorn et al (1987, Diamantino et al (2000), Muyssen and Janssen (2004) and Martínez-Jerónimo et al (2006). We used soft reconstituted water (44 mg l -1 CaCO 3 ) with a pH value of 7.2 as zooplankton culture media in the toxicity tests, while the cited authors have used hard (160-180 mg l -1 CaCO 3 ) or very hard (280-320 mg l -1 CaCO 3 ) reconstituted water with pH higher than 7.6 in their experiments.…”
Section: Discussioncontrasting
confidence: 70%
“…Table 2 summarizes some results of 48 h-LC 50 values for metals to daphnid species, however, the different physical and chemical parameters of culture media (hardness, and pH), make comparisons difficult. We obtained 48 h-LC 50 values for cadmium and chromium to D. similis lower than those that have been obtained for other daphnid species by Fargasová (1994), Barata et al (1998), Taylor et al (1998), Dorn et al (1987, Diamantino et al (2000), Muyssen and Janssen (2004) and Martínez-Jerónimo et al (2006). We used soft reconstituted water (44 mg l -1 CaCO 3 ) with a pH value of 7.2 as zooplankton culture media in the toxicity tests, while the cited authors have used hard (160-180 mg l -1 CaCO 3 ) or very hard (280-320 mg l -1 CaCO 3 ) reconstituted water with pH higher than 7.6 in their experiments.…”
Section: Discussioncontrasting
confidence: 70%
“…At higher temperatures, the antagonistic behaviour given by the interpretation of model parameters was not confirmed by the LC 50 values calculation, where the values decreased with an increase of temperatures (Table 3). Synergistic effects are usually associated to extreme environmental conditions, as HT, by directly and/or indirectly increase the toxicity of chemicals, as reported by several studies (Folt et al 1999, Heugens et al 2003, Heugens et al 2006, Lewis and Horning 1991, Martinez-Jeronimo et al 2006. The increase of nickel toxicity at high temperatures might also be related to an increase in metabolism and destabilisation of homeostasis (Lannig et al 2006).…”
Section: Combined Exposuresmentioning
confidence: 96%
“…Although other authors have reported higher values as, for example, 1.3 mg l -1 Enserink et al (1990), 0.64 mg l -1 (Van Leeuwen et al 1987), or 0.35 mg l -1 (Bulus and Ronco 1996). Martínez-Jerónimo et al (2006) determined LC 50 values of 0.2076 ± 0.0164 and 0.1544 ± 0.0175 mg l -1 at 20 and 25°C, respectively, which are similar to those obtained herein, confirming that D. magna is a species sensitive to Cr(VI).…”
Section: Discussionmentioning
confidence: 90%